Figurations of Alterity: an Encounter with the Archive - Frida Gorbach (Glocalism: Journal of Culture, Politics and Innovation)
In this work I ponder about the archive based on three images from the late nineteenth and early twentieth centuries: the drawing of a monster from the Teratology collection of the Museo Nacional de México preserved today in the Biblioteca Nacional de Antropología e Historia; the photography of animals that are part of what was the collection of the Museo de Historia Natural del Chopo and that today protects the Fototeca Nacional; and the copy of a drawing of a hysterical woman that is part of the iconography of the French hospital de la Salpêtrière and that was reproduced in Mexico in a scientific journal. With the perspective offered by the “archival turn”, these individual images speak about the procedures of classification, hierarchy and exclusion that organized the knowledge system. They also show three ways of articulating madness, the bestial and the primitive, three figures of the Other from the West, three paths that lead to the “Indian”, that descendant of the pre-Hispanic inhabitants of the American continent on whose erasure was erected the scientific normalizing discourse and the nation-state.